Термин «общественные организации» в конституционном законодательстве Украины - Волкова Дарія Євгенівна; Волкова Дарья Евгеньевна; Volkova Dariya (My University, 2014)
The article characterized argues that the current Ukrainian legislation on NGOs needs 2 definitions of the term “non-governmental organization”, as it is neither productive nor even possible to give a unified one. It is because the Ukrainian constitutional legislation is harmonized with the European standards on NGOs now. While this harmonization lasts, the normative definition (the first one) should be constituted according to the terms of the current Ukrainian legislation. The second definition should be a prospective one, and should be harmonized with the European standards on NGOs. When the harmonization of the Ukrainian legislation on NGOs will be finished, only one (prospective) definition will be left.
Волкова Д. Е. Термин «общественные организации» в конституционном законодательстве Украины / Д. Е. Волкова // «Legea si Viata» : междун. научно-практ. правовой журнал. - 2014. - №11. - С.35-39.
Keywords: гражданское общество; общественные организации; неправительственные организации; объединения граждан; неправительственные объединения; цивільне суспільство; громадські організації; неурядові організації; об'єднання громадян; неурядові об'єднання; civil society; non-governmental organizations; institutions of the civil society; non-commercial organizations